The effect of hybrid SCMC (BYOD) on foreign language anxiety and learning experience in comparison to pure SCMC and FTF communication - Liu, Xuecheng (Frontiers in Psychology, 2023)
This study aims to investigate the impact of using synchronized computer-mediated communication (SCMC) in a face-to-face (FTF) classroom on reducing foreign language anxiety (FLA) and enhancing the learning experience. Fifty Chinese college students participated in a learning activity under three modes: normal FTF classroom (the blank sample), pure SCMC, and hybrid SCMC (BYOD). Smartphones, PCs, open internet, and the bring-your-own-device (BYOD) concept were used for SCMC applications. After completing the learning activity, the students completed Foreign Language Classroom Anxiety Scale (FLCAS) questionnaires. The students were also asked to complete perceptual questionnaires to assess their interaction, anxiety, distraction from the internet, and class atmosphere in the three modes. The results showed that the hybrid SCMC (BYOD) resulted in better interaction than the normal FTF classroom mode (the blank sample), while pure SCMC showed no significant improvement. Both SCMC modes reduced FLA compared to the normal FTF classroom mode (the blank sample), but pure SCMC caused a noticeable increase in distraction from the internet and weakened the classroom atmosphere. In contrast, the hybrid SCMC (BYOD) mode slightly increased distraction and improved the classroom atmosphere.